2007
DOI: 10.1007/s10549-007-9675-8
|View full text |Cite
|
Sign up to set email alerts
|

Parity and disparity in first course treatment of invasive breast cancer

Abstract: Our findings suggest treatment standards are not adequately or equivalently met among Black and White women, even in an area where teaching hospitals provide a substantial portion of breast cancer care. Treatment differences can adversely affect outcome and reasons for the differences need to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
101
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 52 publications
12
101
0
Order By: Relevance
“…Because of the limited follow-up period, currently, we cannot appropriately assess this but will continue follow-up. In combination with our knowledge of the treatment among those tested with the RS (and those not tested; data not shown), racial differences in outcome among ER-positive/lymph node-negative patients reported by others, 4,5,11,12,23 thus, may be related to treatment efficacy, eg, endocrine agent metabolism, 24 as well as under treatment, 5-7 treatment compliance, [5][6][7] and differences in established prognostic factors or underlying tumor biology. 4,10 Currently, we are investigating the potential for differences in endocrine agent metabolism.…”
Section: February 1 2012mentioning
confidence: 66%
“…Because of the limited follow-up period, currently, we cannot appropriately assess this but will continue follow-up. In combination with our knowledge of the treatment among those tested with the RS (and those not tested; data not shown), racial differences in outcome among ER-positive/lymph node-negative patients reported by others, 4,5,11,12,23 thus, may be related to treatment efficacy, eg, endocrine agent metabolism, 24 as well as under treatment, 5-7 treatment compliance, [5][6][7] and differences in established prognostic factors or underlying tumor biology. 4,10 Currently, we are investigating the potential for differences in endocrine agent metabolism.…”
Section: February 1 2012mentioning
confidence: 66%
“…34 Several studies have revealed disparities because of race/ethnicity, older age, and geographic location in breast cancer care, including the receipt of RT after BCS. 12,13,27,[35][36][37][38][39][40][41][42][43] The present study, however, is the first to document a disparity in the receipt of RT because of race/ethnicity and SES in a single region within the state of California, and an age disparity throughout the entire state. LA, the most populous of the California regions with the largest number and highest percentage of African American and Hispanic residents in this study, is the only region where the association of RT after BCS varied by race/ethnicity.…”
Section: Discussionmentioning
confidence: 88%
“…And this study's hypothesized African American disadvantage among younger women was not only observed for survival, but also for receipt of a number of treatments. This study could also be limited by the known incompletion of its chemo and hormonal therapy data: 8% and 4%, respectively [64]. Again, we think its pattern of findings not to be potently confounded.…”
Section: Study Limitations and Strengthsmentioning
confidence: 84%